Efektifitas Pijat Perineum Terhadap Ruptur Persalinan di PMB Sri Winarni - King King Hoerunisach; Gusrida Umairo; Abela Mayunita (Journal of Innovative and Creativity, 2025)
Rupture is an obstetric tear that occurs due to the inability of the pelvic muscles and soft tissues during normal labor (Fatimah et al., 2019). Perineal rupture is more likely to occur in mothers with primiparous births, large fetuses, long labor processes, or labor with the help of tools, such as forceps or vacuum (Adrian in Kartiningsih, et al., 2021). At PMB Sri Winarni, the number of rupture incidents in 2022 was 66 cases, an increase from 2021 which was 40 cases. The data on rupture incidents recorded from early 2023 to the present, amounted to 25 cases. One effort to prevent rupture is to perform perineal massage. Perineal massage is performed during pregnancy or a few weeks before giving birth to increase hormonal changes that soften the connective tissue, so that the perineal tissue is more elastic and easier to stretch. To determine the effectiveness of perineal massage on perineal rupture in mothers giving birth at PMB Sri Winarni. This research is quantitative analytical and has a Quasi Experimental Design (quasi-experimental) research design. The use of Purposive Sampling Technique with a total of 20 respondents. This study uses the Perineal Massage variable as the independent variable, and the Perineal Rupture variable as the dependent variable. The data used were obtained from observation sheets and questionnaires which were then analyzed using the Independent Sample T Test analysis in the SPSS program. Of the 20 respondents, 12 people (60%) did not experience perineal rupture, there were 6 people (30%) who experienced grade 1 rupture, and 2 people (10%) experienced grade 2 perineal rupture. And based on the calculation of the Independent Sample T Test, the Asymptotic Significance value (2-sided) = 0.008 was obtained where <0.05. So it can be concluded that H0 is rejected and Ha is accepted, which indicates the Effectiveness of Perineal Massage on Perineal Rupture in Mothers Giving Birth at PMB Sri Winarni.